COVID-19-associated myocarditis presenting as new-onset heart failure and atrial fibrillation. Issue 7 (12th July 2021) - Gaine, Sean; Devitt, Patrick; Coughlan, John Joseph; Pearson, Ian
Abstract : A 58-year-old man presented to the emergency department with recent-onset palpitations and progressive exertional dyspnoea. ECG demonstrated new-onset atrial fibrillation. Transthoracic echocardiogram showed global impairment in left ventricular systolic function with left ventricular ejection fraction of 20%. Cardiac MRI (CMRI) demonstrated generalised severe myocarditis. A SARS-CoV-2 PCR was positive for SARS-CoV-2 RNA. As such, we diagnosed our patient with COVID-19-associated myocarditis based on CMRI appearances and positive SARS-CoV-2 swab. This case highlights that COVID-19-associated myocarditis can present as new atrial fibrillation and heart failure without the classic COVID-19-associated symptoms.